2023
DOI: 10.5194/egusphere-2022-1444
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A simple model to assess the impact of gravity waves on ice crystal populations in the tropical tropopause layer

Abstract: Abstract. The role of gravity waves on microphysics of tropical cirrus clouds and air parcel dehydration was studied using the combination of Lagrangian observations of temperature fluctuations and a 1.5 dimension model. High frequency measurements during isopycnal balloon flights were used to resolve the gravity wave signals with periods ranging from a few days to 15 min. The detailed microphysical simulations with homogeneous freezing, sedimentation and a crude horizontal mixing represent the slow ascent of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Some of the balloons carry a microlidar system that can detect even the thinnest TTL cirrus (Ravetta et al, 2020). Dynamical information inferred from balloons has already been used in several studies of TTL cirrus (Jensen et al, 2016;Corcos et al, 2023) and offers further insight into the tropical cirrus life cycle Sect. 6.3.…”
Section: In Situ Measurementsmentioning
confidence: 99%
“…Some of the balloons carry a microlidar system that can detect even the thinnest TTL cirrus (Ravetta et al, 2020). Dynamical information inferred from balloons has already been used in several studies of TTL cirrus (Jensen et al, 2016;Corcos et al, 2023) and offers further insight into the tropical cirrus life cycle Sect. 6.3.…”
Section: In Situ Measurementsmentioning
confidence: 99%
“…As noted above, previous modeling studies investigated the influence of waves on ice nucleation and showed that high‐frequency gravity waves can enhance ice concentrations in cirrus (Corcos et al., 2023; Jensen et al., 2010; Spichtinger & Krämer, 2013). Here, we show that the influence of waves after ice nucleation has ceased is to decrease ice concentrations.…”
Section: Summary and Discussionmentioning
confidence: 96%
“…(2016) developed probabilistic models describing the MTF. We note that previous studies have directly used the super‐pressure balloon temperature time series for simulations of temperature fluctuation influence on TTL cirrus (Corcos et al., 2023; Dinh et al., 2016). Whereas we are using ensembles of the essentially equivalent synthetic temperature time series.…”
Section: Impact Of Stochastic Mesoscale Temperature Fluctuationsmentioning
confidence: 99%
“…Clearly, compared to idealized simulations based on constant updrafts, the GW forcing of ice supersaturation results in a more realistic evolution of cirrus clouds. In particular, stochastic cooling and warming phases act to extend cirrus lifetimes compared to a constant, slow updraft scenario (Corcos et al., 2023). In our specific case, a small range of ice crystal radii around 20 μm happens to be a sweet spot in the MUT PSD that is neither significantly affected by sublimation nor by sedimentation over 3 hr of simulation time.…”
Section: Idealized Simulationsmentioning
confidence: 99%